2007
DOI: 10.1016/j.gca.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

A large metabolic carbon contribution to the δ13C record in marine aragonitic bivalve shells

Abstract: It is well known that the incorporation of isotopically light metabolic carbon (C M ) significantly affects the stable carbon isotope (d 13 C) signal recorded in biogenic carbonates. This can obscure the record of d 13 C of seawater dissolved inorganic carbon (d 13 C DIC ) potentially archived in the shell carbonate. To assess the C M contribution to Mercenaria mercenaria shells collected in North Carolina, USA, we sampled seawater d 13 C DIC , tissue, hemolymph and shell d 13 C. All shells showed an ontogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 60 publications
4
129
0
1
Order By: Relevance
“…It is important to note that these predictions are only applicable to range of sizes and at the salinity/alkalinity of the current experiments. Additionally, had this relationship been determined for the Florida hatchery Mercenaria hybrids (based on the limited data we have), a smaller size at which dissolution pressure could be overcome would have been found in hard clams indicate that larger/older clams utilize more respired CO 2 for calcification versus smaller/ younger clams (Elliot et al 2003, Lorrain et al 2004, Gillikin et al 2007). Although to date little is known about the isotope ratios in early juvenile shells, the increase in respired C in shell material deposited with age suggests the potential importance of feeding physiology on calcification.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that these predictions are only applicable to range of sizes and at the salinity/alkalinity of the current experiments. Additionally, had this relationship been determined for the Florida hatchery Mercenaria hybrids (based on the limited data we have), a smaller size at which dissolution pressure could be overcome would have been found in hard clams indicate that larger/older clams utilize more respired CO 2 for calcification versus smaller/ younger clams (Elliot et al 2003, Lorrain et al 2004, Gillikin et al 2007). Although to date little is known about the isotope ratios in early juvenile shells, the increase in respired C in shell material deposited with age suggests the potential importance of feeding physiology on calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the isotopic composition of respired and environmental carbon offer an alternative proxy for metabolic rate, which is recorded in the isotopic composition of biomineral carbonate and thus applicable to deep time studies. Ecogeochemical proxies for organism field metabolic rate revolve around the proportion of respired carbon present in blood fluids during deposition of biominerals [56][57][58]. In fishes, carbon in the blood is derived from dissolved inorganic carbon ingested via the gills and stomach and from carbon released by the cellular respiration of ingested food nutrients.…”
Section: Metabolic Ratementioning
confidence: 99%
“…Some studies have argued that δ 13 C ar is controlled by the δ 13 C DIC in water, (e.g., Mook, 1971;Fritz and Poplawski, 1974), many others have suggested that both kinetic and metabolic effects play an important role in determing δ 13 C ar (Keith et al, 1964;Tanaka et al, 1986;Klein et al, 1996;McConnaughey et al, 1997;Dettman et al, 1999;Lorrain et al, 2004;Gillikin et al, 2006Gillikin et al, , 2007Gillikin et al, , 2009. Kinetic isotope effects refer to the simultaneous depletion of 18 O and 13 C associated with fractionation during CO 2 hydration and hydroxylation (McConnaughey, 1989).…”
Section: Shell δmentioning
confidence: 99%
“…Metabolic controls on the incorporation of various sources of carbon, such as from respiration or food, into shell carbonate can produce such isotope effects. Metabolic carbon represented a small portion (~10%) of the carbon deposited in molluscan shell carbonate (McConnaughey et al, 1997;Kennedy et al, 2001;Lorrain et al, 2004;Gillikin et al, 2005) and more recently up to 37% (Gillikin et al, 2007). Studies show that contribution of metabolic carbon can dampen the δ 13 C DIC signal recorded in shells and explain δ 13 C ar disequilibrium in bivalves (Krantz et al, 1987;Klein et al, 1996;Keller et al, 2002;Lorrain et al, 2004;Gillikin et al, 2007).…”
Section: Shell δmentioning
confidence: 99%
See 1 more Smart Citation